2010
DOI: 10.1002/humu.21189
|View full text |Cite
|
Sign up to set email alerts
|

Plectin expression patterns determine two distinct subtypes of epidermolysis bullosa simplex

Abstract: Plectin is a cytoskeletal linker protein that has a dumbbell-like structure with a long central rod and N- and C-terminal globular domains. Mutations in the gene encoding plectin (PLEC1) cause two distinct autosomal recessive subtypes of epidermolysis bullosa (EB): EB simplex with muscular dystrophy (EBS-MD), and EB simplex with pyloric atresia (EBS-PA). Here, we demonstrate that normal human fibroblasts express two different plectin isoforms including full-length and rodless forms of plectin. We performed det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
64
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(66 citation statements)
references
References 50 publications
(53 reference statements)
2
64
0
Order By: Relevance
“…32 We therefore confirmed presence of the rodless domain by sequencing cDNA and used realtime PCR to compare the relative abundance of the rodless transcript in P1, P2, and 3 normal controls. The rodless transcript/full transcript ratio was 0.15 in P1, 0.32 in P2, and 0.22 Ϯ 0.03 (mean Ϯ SD) in 3 controls.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…32 We therefore confirmed presence of the rodless domain by sequencing cDNA and used realtime PCR to compare the relative abundance of the rodless transcript in P1, P2, and 3 normal controls. The rodless transcript/full transcript ratio was 0.15 in P1, 0.32 in P2, and 0.22 Ϯ 0.03 (mean Ϯ SD) in 3 controls.…”
Section: Resultsmentioning
confidence: 89%
“…It has been suggested that expression of the rodless transcript can mitigate the phenotype in patients who carry mutations in the plectin rod domain. 32 However, real-time PCR indicates that expression of the rodless transcript was higher in the more severely affected P2. Thus in the patients studied by us the abundance of the rodless transcript was not a reliable indicator of the clinical phenotype.…”
Section: Resultsmentioning
confidence: 99%
“…Almost half of the patients (20) were homozygotes. In summary, 54 different mutations in eight exons (9,14,19,21,22,24,31,32) and in three introns (i11, i25, i30) were found by DNA molecular analysis. Mutations were mostly located in exons 31 (69% of all mutations) and 32 (14% of all mutations), see Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…In these patients the full-length plectin is absent, but they typically express a rodless plectin isoform, which delays the onset of MD because of the remaining IFbinding site. 13,14 In EBS-PA patients the more severe disease phenotype is caused by the fact that both full-length and rodless plectin isoforms are deficient. 15 So far, 49 patients with EBS-MD have been described in the literature (our patient included).…”
Section: Discussionmentioning
confidence: 99%
“…Patients exhibit severe skin blistering with gastric abnormalities, particularly pyloric or duodenal atresia (Nakamura et al, 2005). Most EBS-MD patients have mutations in exon 31 encoding the plectin rod domain and it may be that expression of the rodless isoform, which is maintained in these patients, alleviates skin blistering symptoms (which are much less severe than those in patients with EBS-PA) and delays the onset of muscle weakness (Natsuga et al, 2010). It is worth noting that mutations in ITGA6 and ITGB4, encoding the hemidesmosomal integrin subunits a 6 and b 4 respectively, can result in another form of EB, junctional EB-PA. EBS-Olga is an autosomal dominant disease that is characterised by skin blistering, predominantly on the hands and feet, and generalised bruising.…”
Section: Diseases Of Plectin and Bpag1mentioning
confidence: 99%